A revolta contra a utilidade : a improdutividade em suas diversas facetas na obra de Georges Bataille - Araujo, Pedro Antônio Gregorio de (2021)
The present work attempts to analyze the concept of unproductivity theorized by the philosopher Georges Bataille (1897-1962), who analyzes it in its various fields. In this work we will have as main axes of conceptualization of unproductivity religion, anthropology, economics and literature. Our hypothesis is to use the phenomenon of unproductivity as a reading key for understanding the philosopher's thought, and we propose to demonstrate how this relates and underlies the idea of freedom affirmed by the thinker, namely the critique of the ideology of utility and productivism, foundation governing the capitalist world. Therefore opening the possibility of a being that spends in a sumptuous way to the point of breaking with the chains around it, making concepts originated from rationality and the world of work null. Our methodology is the bibliographic research of works by Georges Bataille, books of authors related to his thought, and also texts by commentators of his philosophy. We hope as a result to realize a constellation of Bataillian concepts, of the thinkers who were the inspiration for their theory, and, finally, to bring his thinking to contemporary times.